Development and implementation of a national antimicrobial stewardship surveillance system, with open access data sharing. (January 2021) - Ashiru-Oredope, D.; Budd, E.L.; Doble, A.; Cramp, E.; Hendrick, A.; Hopkins, S.
Summary: Background: Public Health England (PHE) developed an antimicrobial stewardship (AMS) surveillance system and conducted a national pilot to test the feasibility of centrally collecting data from AMS audits performed by NHS hospital trusts. The system was simplified, focusing on requirements of the NHS AMR CQUIN (Commissioning for Quality and Innovation; a financial incentive quality improvement scheme). Aim: To present results and user feedback from the national pilot, and results from using the AMS surveillance system as part of the AMR CQUIN. Methods: An AMS surveillance system was developed and a national pilot conducted in which 33 NHS trusts submitted data and feedback on system utilization. The system was refined based on feedback and deployed nationally to collect AMS data for the 2016–17 AMR CQUIN. Findings: Most trusts participating in the pilot collected data on documentation of indication (90%). Fewer collected data on documenting review decisions at 48–72 h (36%). On average 83% of patients had an indication documented, whereas 71% had formal documentation of 48–72 h review. AMR CQUIN data were submitted by 88% of trusts for at least one quarter of 2016–17. Approximately 92% of prescriptions had an indication documented and 87.5% of prescriptions had evidence of review within 72 h; these increased by 7 and 10 percentage points respectively between the first and final quarters. Conclusion: The AMS surveillance system allowed AMS audit data from NHS trusts in England to be collected centrally. PHE publishes these data openly online, on PHE Fingertips portal, a national public health data portal. The reported data highlight improvement in the percentage of antibiotic prescriptions with evidence of a documented review within 72 h.